2022
DOI: 10.1038/s41598-022-15729-y
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-particles interactions during composite particles formation by pulsed laser melting of α-Fe2O3

Abstract: This work thoroughly investigates chemical solvent-particles interactions during the formation of composite particles by pulsed laser melting of α-Fe2O3. Two solvents, with different dielectric constants, such as ethyl acetate (εr = 6) and ethanol (εr = 24.6), were examined in terms of their effect on the morphology, size, and phase composition of iron oxide composites. We calculated the laser fluence curves using the heating-melting-evaporation approach to identify the critical particle size that undergoes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Phase diagrams calculated as the dependence of particle size on the required laser fluence J for Fe 2 O 3 systems explain the differences in the results obtained at two different wavelengths. In the case of the 2nd harmonic, as shown in previous work [21], the laser fluence has a minimum value of 200 mJ/pulse cm 2 for particles with a diameter of about 200 nm. The calculations shown in Fig.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Phase diagrams calculated as the dependence of particle size on the required laser fluence J for Fe 2 O 3 systems explain the differences in the results obtained at two different wavelengths. In the case of the 2nd harmonic, as shown in previous work [21], the laser fluence has a minimum value of 200 mJ/pulse cm 2 for particles with a diameter of about 200 nm. The calculations shown in Fig.…”
Section: Resultssupporting
confidence: 58%
“…The size, morphology, and composition of obtained particles can be tuned in a controllable manner by experimental parameters, such as wavelength, laser fluence, irradiation time, solvent, and molar ratio of irradiated materials [20]. This paper complements earlier reports on the irradiation of α-Fe 2 O 3 nanoparticles dispersed in ethyl acetate [21] by investigating the effects of irradiation using a laser beam in the ultraviolet range with a wavelength of 355 nm (3rd harmonics). By changing the laser fluence and irradiation time, α-Fe 2 O 3 is reduced to Fe 3 O 4 , FeO, and Fe.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…This process is alternatively repeated during pulsed laser irradiation of suspensions (PLIS), initially known as pulsed laser melting in liquid (PLML). [14][15][16][17][18][19][20] In 2007, Ishikawa et al [21] reported for the To display phase diagrams with the functionality of laser/suspension parameters, the reaction first time that unlike the laser ablation process used to produce smaller nanoparticles, PLML uses lower laser fluences and forms larger particles than the original constituents by melting. Later, an absorption model was introduced to calculate the temperature of suspended particles irradiated by a pulsed laser [22] followed by the addition of a cooling term to the model to calculate the temperature even more accurately.…”
Section: Introductionmentioning
confidence: 99%